2003
DOI: 10.1108/eb008749
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Confirmation of Wine‐Related Lifestyle Segments in the Australian Wine Market

Abstract: The wine industry has been criticised in the past for adopting a mass‐marketing approach but in the current ultra‐competitive wine market the inevitable outcome of a production rather than marketing orientation is almost certain failure. Whereas the Australian domestic wine market is currently experiencing a low growth rate, a precursor to any future growth strategy is a clear understanding of the market. Acceptance of market segmentation as a strategy to target consumers more effectively enhances the focus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 5 publications
10
86
1
2
Order By: Relevance
“…For instance, a consumer who reports 25 years of wine drinking experience may not have the same level of knowledge or involvement in wine than someone with far fewer years of experience. Conversely, objective wine knowledge, as measured by Johnson and Bruwer (2003), does not take into account the exposure associated with higher consumption volume and greater periods of time drinking wine. Solomon (1990) used two consumer segments to investigate wine related communication, one with industry involvement termed 'experts', and one with no industry experience, termed 'novices'.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, a consumer who reports 25 years of wine drinking experience may not have the same level of knowledge or involvement in wine than someone with far fewer years of experience. Conversely, objective wine knowledge, as measured by Johnson and Bruwer (2003), does not take into account the exposure associated with higher consumption volume and greater periods of time drinking wine. Solomon (1990) used two consumer segments to investigate wine related communication, one with industry involvement termed 'experts', and one with no industry experience, termed 'novices'.…”
Section: Introductionmentioning
confidence: 96%
“…The number of respondents with tertiary qualifications (76.8%) was greater than in the general population, 24 but again consistent with other studies that demonstrated wine consumers are more likely to hold tertiary qualifications. 16,25,26 This was also reflected in respondents' household incomes; ~50% of respondents had an average household income above 100,000 AUD, with the majority of participants' household earnings exceeding the 64,168 AUD per annum Australian median household income. 27 segmentation of wine consumers according to their oak knowledge…”
Section: Demographic Characteristics Of Consumersmentioning
confidence: 99%
“…Instead, wine-related consumer studies have tended to focus on purchase drivers, product involvement, and wine expertise. 14,[16][17][18] Lockshin and Rhodus investigated the influence of price and oak flavor on the perception of wine quality and found that consumers had no real preference for oak, whereas wine wholesalers held oak maturation in much higher regard, particularly with respect to the marketability of wine. 19 A more recent study evaluated consumer preferences for wines aged in oak barrels or with oak chips.…”
mentioning
confidence: 99%
“…Extant academic literature has focused primarily on the globalization of wine industry and its implications for the U.S. wine industry Castaldi et al, 2004;Silverman et al, 2003). There have been quite a few rigorous academic studies of wine consumers in Australia and New Zealand, such as Bruwer et al, (2002); Thomas and Pickering, (2003); Johnson and Bruwer, (2003). These papers employ various segmentation techniques to enhance their understanding of domestic consumers as well as provide important recommendations for their domestic producers.…”
Section: Significance Of the Studymentioning
confidence: 99%